Pengaruh Filsafat Hukum Terhadap Dinamika Pembentukan Hukum Modern - Yuwono Prianto; Frangky Jonatan; Vinshen Saputra; Lena Mariana Br Sitorus (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Legal philosophy plays an important role in bridging the relationship between law, society, and changing times. Rooted in the principle of "ubi societas, ibi ius" which emphasizes that law and society are complementary entities, this study explores the dynamics of legal philosophy in the digital era. Normative research methods with philosophical and conceptual approaches are used to explore how basic values such as justice, human rights, and utilitarianism are adapted in the modern legal system. The digital era presents new challenges, such as data privacy, cybersecurity, and digital justice. Legal philosophy is expected to be able to develop a new conceptual framework to adapt to technological realities, including the use of artificial intelligence (AI) and big data in law enforcement. In addition, the role of legal philosophy is also seen in the development of relevant regulations, such as the protection of personal data and electronic transactions, to answer the needs of the digital era society. The history of legal philosophy shows a significant evolution of thought from ancient Greece to the modern era, which continues to be relevant in supporting the legitimacy of law and justice. In this era, legal philosophy combines ethics with technology to ensure the inclusivity, transparency, and sustainability of the legal system. This study highlights the importance of technology integration in legal education, improving digital regulations, and innovation of the justice system to maintain access to justice amidst social change.